2021
DOI: 10.31253/pe.v19i1.505
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Information Asymmetry, Company Size And Managerial Ownership On Income Management (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange)

Abstract: Earnings Management is the action of a manager by presenting reports that increase or decrease profit for the current period of the business unit for which is responsible, without causing an increase or decrease in the unit's long-term economic profitability. The purpose of this study was to examine the effect of information asymmetry, Company Size and Management ownership of Earnings Management in various industry sector companies listed on the Indonesia Stock Exchange 2017-2019. The sample used in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In contrast, a range of studies depicted that large firms usually have up-to-date internal control systems, as a result, less likely to incur earnings management (Kim, Chung, & Firth, 2003;Chandra & Wimelda, 2018;Zouari, Lakhal, & Nekhili, 2015). Moreover, I also use some other factors as previous studies found ambiguous results regarding these variables, such as firm financial leverage (Chandra & Wimelda, 2018;Kordestani & Mohammadi, 2016;Lemma, Negash, Mlilo, & Lulseged, 2018), return on assets (Lopes, 2018;Laksmana & Yang, 2014); market to book ratio (El Guindy & Basuony, 2018); average operating cycle (Kordestani & Mohammadi, 2016); product market power (Datta, Iskandar-Datta, & Singh, 2013); loss dummy and External financing (Zhang, Uchida, & Dong, 2020); debt maturity structure (Lemma, Negash, Mlilo, & Lulseged, 2018); managerial ownership (Sumantri, Kusnawan, & Anggraeni, 2021;Al-Fayoumi, Abuzayed, & Alexander, 2010); lagged total accruals (Muttakin, Khan, & Azim, 2015;Koh, 2003); Tobin's Q (Muttakin, Khan, & Mihret, 2017). I present the variable definition in Table 2, and sketch the data and disclose descriptive statistics in the subsequent part.…”
Section: Real Earnings Management (Rem) =∑Cfomentioning
confidence: 99%
“…In contrast, a range of studies depicted that large firms usually have up-to-date internal control systems, as a result, less likely to incur earnings management (Kim, Chung, & Firth, 2003;Chandra & Wimelda, 2018;Zouari, Lakhal, & Nekhili, 2015). Moreover, I also use some other factors as previous studies found ambiguous results regarding these variables, such as firm financial leverage (Chandra & Wimelda, 2018;Kordestani & Mohammadi, 2016;Lemma, Negash, Mlilo, & Lulseged, 2018), return on assets (Lopes, 2018;Laksmana & Yang, 2014); market to book ratio (El Guindy & Basuony, 2018); average operating cycle (Kordestani & Mohammadi, 2016); product market power (Datta, Iskandar-Datta, & Singh, 2013); loss dummy and External financing (Zhang, Uchida, & Dong, 2020); debt maturity structure (Lemma, Negash, Mlilo, & Lulseged, 2018); managerial ownership (Sumantri, Kusnawan, & Anggraeni, 2021;Al-Fayoumi, Abuzayed, & Alexander, 2010); lagged total accruals (Muttakin, Khan, & Azim, 2015;Koh, 2003); Tobin's Q (Muttakin, Khan, & Mihret, 2017). I present the variable definition in Table 2, and sketch the data and disclose descriptive statistics in the subsequent part.…”
Section: Real Earnings Management (Rem) =∑Cfomentioning
confidence: 99%
“…Schift and Lewin in [3] state that agents (management) are in positions that have more information about their capacity, work environment and the company as a whole than principals (company owners). Assuming that individuals are acting to maximize their own self-interest, the information asymmetry they have encourages the agent to hide some information that the principal does not know so that in such conditions the principal is often at a disadvantage.…”
Section: Introductionmentioning
confidence: 99%